False colours ebook - Heyer, Georgette (Regency Romances, 2008)
The Queen of Regency Romance, bestselling author Georgette Heyer, charms readers with this delightful romp of mistaken identity. A missing twin Something is very wrong, and the Honourable Christopher "Kit" Fancot can sense it. Kit returns to London on leave from the diplomatic service to find that his twin brother Evelyn has disappeared and his extravagant mother's debts have mounted alarmingly. A quick-minded heiress The Fancot family's fortunes are riding on Evelyn's marriage to the self-possessed Cressy Stavely, and her formidable grandmother's approval of the match. If Evelyn fails to meet the Dowager Lady Stavely in a few days as planned, the betrothal could be off. A fortune in the balance When the incorrigible Lady Fancot persuades her son to impersonate his twin (just for one night, she promises) the masquerade sets off a tangled sequence of events that engage Kit's heart far more deeply than he'd ever anticipated with his brother's fiancée—who might know much more about what's going on than she cares to reveal... Praise for Georgette Heyer: "A writer of great wit and style... I've read her books to ragged shreds."—Kate Fenton, Daily Telegraph "Reading Georgette Heyer is the next best thing to reading Jane Austen."—Publishers Weekly